C. trachomatis-infection accelerates metabolism of phosphatidylcholine derived from low density lipoprotein but does not affect phosphatidylcholine secretion from hepatocytes - Hatch, Grant M (BioMed Central, 2004)
BACKGROUND: Chlamydia trachomatis is a prevalent sexually transmitted disease and the leading cause of infectious blindness in developing nations. It was not known if C. trachomatis-infection influenced metabolism of lipoprotein-derived phospholipids. Nor was it known if C. trachomatis-infection altered phosphatidylcholine (PC) secretion from hepatocytes. In the current study, low density lipoprotein (LDL)-derived [methyl-(3)H]PC metabolism was examined in L929 cells infected with C. trachomatis to determine if PC derived from LDL could serve as a potential source of PC trafficked to C. trachomatis. In addition, release of endogenously synthesized [methyl-(3)H]PC into the medium was examined in rat liver hepatocytes infected with C. trachomatis to determine if infection altered PC secretion. RESULTS: L929 cells 20 h post infection exhibited a 39% (p < 0.05) reduction in radioactivity in PC but total radioactivity incorporation was unaltered compared to controls. Lysophosphatidyl [methyl-(3)H]choline (LPC) and aqueous [methyl-(3)H]choline metabolites were elevated 3.6-fold (p < 0.05) and 16.5-fold (p < 0.05), respectively, in C. trachomatis-infected cells and this was due to a 51% increase (p < 0.05) in calcium-dependent phospholipase A(2 )activity. Hepatocytes 22 h post infection then incubated for 16 h with [methyl-(3)H]choline showed elevated [methyl-(3)H]PC biosynthesis but [methyl-(3)H]PC secreted into the medium was unaltered compared to controls. In contrast, both cellular and medium lyso [methyl-(3)H]PC were elevated in C. trachomatis-infected cells. CONCLUSION: This study is the first to show that metabolism of LDL-derived PC is accelerated in C. trachomatis infection and to support the notion that LDL-delivered PC may potentially serve as a source of PC trafficked to Chlamydia. In addition, C. trachomatis-infection does not inhibit PC secretion from hepatocytes indicating that the pool of newly synthesized PC destined for lipoprotein secretion may differ from the pool of PC used for C. trachomatis membrane biosynthesis.